Protocol of the follow-up of patients with transthyretin amyloid cardiomyopathy by multimodality imaging (FAITH) study: a prospective observational study in patients with ATTR-CM undergoing treatment with tafamidis - Bettina Heidecker; Jeanette Schulz-Menger; Ingolf Sack; Carsten Schwenke; Jan Gröschel; Gina Barzen; Jasmin Zernikow; Edyta Blaszczyk; Katrin Hahn; Helena F Pernice; Elena Romero Dorta; Phillip van Dijck; et al. (BMJ Open)
Introduction This prospective observational study of patients with transthyretin amyloid cardiomyopathy (ATTR-CM) undergoing treatment with tafamidis aims at identifying quantitative image markers and comparing imaging modalities regarding the follow-up and prognostication of these patients, with the goal of providing a multiparametric score to predict treatment response.Methods and analysis Patients with a board-approved decision to receive tafamidis will undergo, in addition to standard of care, baseline and follow-up cardiovascular magnetic resonance (CMR) scans at 9 and 18 months. In total, the study plans to recruit and scan 60 patients. A blinded read will take place in a CMR research core laboratory. The final statistical analysis will be based on developing a multiparametric score for the prediction of treatment response. The study will be managed through the Amyloidosis Center Charité Berlin, a clinical unit formed from the three clinical campus sites of the Charité in Berlin, using the Berlin Research Network for CMR.Ethics and dissemination The study was approved by the Charité—Universitätsmedizin Berlin ethics committee EA1/262/23. The results of the study will be disseminated through international peer-reviewed publications and congress presentations.Trial registration number Approved WHO primary register: German Clinical Trials Register: https://www.drks.de/DRKS00033884. WHO International Clinical Registry Platform: https://trialsearch.who.int/?TrialID=DRKS00033884. Recruitment started on 1 July 2024.